Corrigendum to “The global burden of suicidal behavior among people experiencing food insecurity: A systematic review and meta-analysis”. - Kaggwa, Mark Mohan; Akatusasira, Rita; Al-Mamun, Firoj; Prat, Sebastien; Mamun, Mohammed A.; Combey, Isabelle; Bongomin, Felix; Harms, Sheila; Chaimowitz, Gary; Griffiths, Mark D.; Olagunju, Andrew T. (Journal of affective disorders, 2024)
The strength of the relationships: “There was a positive relationship between experiencing food insecurity and (i) suicide ideation (aOR=1.078 [95% CI: 1.075-1.082; I2=99.5%, p<0.001, k=30]), (ii) suicide plans (aOR=1.496 [95% CI: 1.257-1.473; I2=91.8%, p<0.001, k=4]), suicide attempts (aOR=1.589 [95% CI: 1.453- 1.737; I2=84.6%, p<0.001, k=14]), and (iii) unspecified suicide behaviors (aOR=1.133 [95% CI: 1.052-1.219; I2=53.0%, p=0.047, k=6]).”
Keywords: Suicidal behavior; Food insecurity; Burden